Os entraves para a Gestão Democrática na rede estadual de ensino de São Paulo - Pereira, Claudia Rosana Campos (2011)
This work aims to present the problem of democratic and participatory management in the structure of the state schools in São Paulo, analyzing the barriers between the bureaucratic machinery of the state and personal relationships that exist in school. Since the promulgation of the Constitution of 1988 and the LDB 9394 of 1996, bringing in their texts the principle of democratic management, it is expected the real implementation of democratic management in the network. The research field has developed in this work help to analyze the scenario in which lies the state schools of São Paulo with regard to democratic and participatory management and what obstacles to it actually occurs.